Bringing Sirukam Dairy to Life: Mascot Design to Boost Tourism Appeal: Menghidupkan Sirukam Dairy: Desain Maskot untuk Meningkatkan Daya Tarik Wisata - Usman, Robby; Bellvania, Sabiya (KPN Kopertis X, 2024)
Sirukam Dairy is a farm-based tourist destination that has seen declining visitor numbers due to the lack of visual promotional media. This study aims to develop a mascot design as a strong and recognizable tourism identity. The mascot is crafted to represent the unique characteristics of Sirukam Dairy, strengthening emotional appeal and enhancing brand awareness. In addition, supporting print media are designed based on graphic design principles to improve visual communication. The presence of the mascot and supporting media is expected to enhance the destination’s image and attract more visitors